Patellar Tendon Avulsion at the Tibial Tubercle at Subacute Stage: A Case Report - Hamza Özer; Asım Ahmadov; Tayfun Özel; Ramazan Düzgün; Gökberk Baki; Salih Erdem (Gazi Medical Journal)
The objective of this case report is to present a rare case of patellar tendon avulsion at the tibial tubercle in a 12-year-old male patient and describe the surgical treatment and rehabilitation process. A 12-year-old male patient with an otherwise healthy status presented with a rupture of the patellar tendon without bony involvement after sustaining a knee injury during a soccer game. Treatment involved a combination of end-to-end suture, support with anchors, and patellar reinforcement using a cerclage wire, a unique approach not previously documented for the pediatric population. Early range of motion exercises were initiated with the use of a functional knee brace. The patient’s progress was assessed through Lysholm and Kujala Scores, as well as a visual analog scale (VAS) for pain. At the final follow-up, conducted 6 months after the surgery, the patient showed satisfactory knee function, with Lysholm and Kujala scores of 85 and a VAS pain score of 0. Radiographic examinations confirmed the successful healing of the patellar tendon with full range of motion in the knee joint. Patellar tendon avulsion at the tibial tubercle is a rare injury in the pediatric population, requiring early diagnosis and prompt surgical treatment to preserve the extensor mechanism and prevent functional loss. The presented combination of end-to-end suture, cerclage wire reinforcement, and anchor support proved effective in this case. This report contributes valuable insights into the treatment of distal patellar tendon avulsion in pediatric patients and emphasizes the importance of appropriate management of such injuries to ensure optimal recovery and knee function. Further research and prospective studies are warranted to validate the efficacy of this surgical approach in larger cohorts.